Health data management practice and associated factors among health professionals working in public health facilities in Oromia Special Zone, Amhara, Ethiopia: a cross-sectional study - Abdu Molla; Mulugeta Hayelom; Kidist Adamu; Mengistu Mera Mihiretu; Yonas Fissha Adem (BMJ Publishing Group, 2024)
Objective Data and information are vital to the decision-making process surrounding health sector reform. In spite of the vast amounts of capital invested in the development of health information systems, health professionals continue to fight with a lack of basic data management skills in Ethiopia. Therefore, this study aimed to assess health data management practices and associated factors among health professionals in public facilities in the Oromia Special Zone, northeast Ethiopia.Method A facility-based cross-sectional survey was conducted among 442 health professionals working in Oromia Special Zone from 8 March 2023 to 28 March 2023. Data were entered into Epi-Data V.4.6, and then it was exported to SPSS V.26 statistical software for processing and analysis. Bi-variable and multivariable logistic regression analyses were computed to see the association between health data management practice and selected independent variables. The bi-variable logistic regression analysis model was used to identify candidate variables for multivariable regression, with a p value <0.2 fitted into the multivariable logistic regression analysis model; a p value less than 0.05 and an adjusted OR (AOR) with a 95% CI were used to declare statistical significance associated with the dependent variable.Results The prevalence of good health data management practices among health professionals was found to be 51.1%, with a 95% CI (45.9 to 55.7). In this study, received training on health data management (AOR=1.82, 95% CI (1.06 to 3.13)), used appropriate technology (AOR=1.78, 95% CI (1.09 to 2.91)) and competency (AOR=6.62, 95% CI (4.06 to 10.80)) were positively associated with health data management practice among health professionals.Conclusion and recommendations Nearly half of health professionals had poor health data management practices. The Zonal Health Department should plan capacity-building training for healthcare professionals, so as to improve their competency. All healthcare facilities should have appropriate and functional health data management technology.